(untitled) (Majalah Kedokteran Bandung, 2021)
Type 2 diabetes is a metabolic disorder caused by insulin resistance and is associated with oxidative stress. In Indonesia, the mean prevalence of diabetes ranges from 1.4% to 1.6%; however, some areas have a much higher diabetes prevalence such as Pekajangan (2.3%) and in Manado (6%). The 2013 Indonesian Basic Health Research (IBHR) stated that the number of people with DM in Indonesia has reached an alarming rate. This study aimed to determine the antidiabetic effect of Polyscias scutellaria on alloxan-induced male Wistar. This was an experimental study conducted in July 2020 in the Faculty of Medicine, Prima Indonesia University. This study used 25 rats that were grouped into 5 treatment groups: control group (Na-CMC), standard (Metformin), and 3 extract groups with different doses (125 mg/kg BW, 250 mg/kg BW, and 500 mg/kg BW). Mangkokan leaf extract was obtained through the maceration method. All ratswere induced intraperitoneally using alloxan monohydrate 10% at a dose of 175 mg/kg BW. The parameters used in this study were fasting blood glucose level before induction, after induction, and after treatment and body weight before treatment. It was observed that there was a significant change in blood glucose level between the extract groups. The blood sugar level in the 125 mg/kg BW group was 495.00 mg/dl while in the 250 mg/kg BW and 500 mg/kg BW, the blood glucose levels were 317.00 mg/dl and 126.00 mg/dl, respectively, with the 500 mg/Kg BW dose as the most effective dose (P-value = 0.001). Thus, mangkokan leaves have the potential to reduce blood glucose level but are not as good as the standard group.